Faktor-faktor yang berhubungan dengan tindakan masyarakat tentang pencegahan demam berdarah dengue di Kecamatan Malalayang Kota Manado - Pioh, Joyseilin Rachela; Rombot, Dina Victoria; Porajow, Zwingly Christian Jefferson Gerard (Jurnal Kedokteran Komunitas dan Tropik, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a significant public health problem at global and local levels, including in Manado City. The Malalayang District reports high case numbers due to population density and environmental conditions that support vector breeding. Although preventive information is easily accessible, community preventive practices remain suboptimal. Aim: To identify the factors associated with community practices in dengue hemorrhagic fever prevention in Malalayang District, Manado City. Methods: A cross-sectional design was used involving 110 respondents selected across three high-risk areas. Data were analyzed using descriptive statistics and chi-square tests. Results: Most respondents were female (57.3%), aged 17–25 years (30.0%), had a senior high school education (49.1%), were in the emerging middle class category (53.6%), and were exposed to dengue-related information (93.6%). Age (p = 0.001) and education level (p = 0.020) were significantly associated with preventive actions, whereas sex (p = 0.843), economic status (p = 0.144), and information exposure (p = 0.966) showed no significant associations. Conclusion: Dengue prevention practices in Malalayang are influenced by age and education level, while sex, economic status, and information exposure are not significantly associated.